Role of inflammatory factor s in the pathology of acute myocardial infarction. (12th October 2011) - An, Zhe; Zhang, Wenqi
Abstract : Objective: To observe the influence of simvastatin on plasma CD40L, MMP-9 and CRP level in patients of acutemyocardial infarction within 1 week. Methods: Sixty one patients of acute myocardial infarction were randomly divided into three groups: simvastatin treatment one group (20 mg/day of simvastatin, n=21), simvastatin treatment two group (80 mg/day of simvastatin, n=23), regular treatment group (no lipid- lowering drugs, n=17). Plasma level of CD40L, MMP-9 and CRP before and after treatment 1 week were detected. At the same time, 35 cases of age matched healthy individuals were selected as a control. Results: Plasma level CD40L, MMP-9 and CRP before treatment in patients of acute myocardial infarction were significantly increased. Plasma level of CD40L, MMP-9 and CRP after treatment by simvastatin were significantly decreased. And plasma level of CD40L, MMP-9 and CRP after treatment by big dose simvastatin were more significantly decreased. Level of plasma lipid were not changed before and after treatment in three groups. Conclusion: Plaque disruption may be related to the increased plasma level of inflammatory factors. Simvastatin decreased plasma level of inflammatory factors in the patients of acute myocardial infarction within the first 7 days, so it may benefit to atherosclerotic plaque stabilisation.